ACETAMIDE COMPLEXES FOR CHLORIDES AND BROMIDES OF SOME LANTHANIDES: SYNTHESIS AND PROPERTIES - L. Yu. Alikberova; D. V. Albov; P. S. Kibalnikov; M. I. Vergeles; G. A. Fedorova; E. V. Volchkova (Тонкие химические технологии, 2016)
The aim of the this work is the synthesis and study (IR, single crystal XRD, DTG) of complex compounds of chlorides and bromides of lanthanum, neodymium, holmium, and erbium with acetamide [Ln(AA)4(H2O)4]Cl3·H2O (Ln = La, Nd, Ho, Er ) and [La(AA)4(H2O)4]Br3·H2O. Ligands (Ln) coordination occurs through the oxygen atoms, and the coordination polyhedra of the Ln atoms are distorted tetragonal antiprisms or two-capped trigonal prisms (CN = 8). All the studied complexes are characterized by a developed system of hydrogen bonds with the bromide or chloride ions (and outer-sphere water molecules) in the cavities of the structure formed by the complex cations. The features of the complexes thermal decomposition are discussed.